Foliar spray of prohexadione-calcium improves the adaptability of mung bean to saline-alkali stress - Liang, Xilong; Dong, Yanlei; Jiang, Qiuyu; Hou, Xue; Song, Yang; Zhao, Fengzhou; Sun, Yu; Jiang, Haipeng; Fang, Shumei; Wang, Qingyan (Frontiers in Plant Science, 2025)
IntroductionSaline-alkali soils are a major constraint to mung bean cultivation and extension, and prohexadione-calcium (Pro-Ca) can enhance plant tolerance to saline-alkali stress.MethodsIn order to explore the regulatory effect and mechanism of Pro-Ca on mung bean growth under saline-alkali stress, the morphology, ultrastructure, physiological indicators, and gene expression were measured in this study.ResultsThe results indicate that Pro-Ca can improve the adaptability of mung bean to saline-alkali stress. Specifically, it manifests as increasing dry matter accumulation, protecting the structural integrity and quantity of organelles such as chloroplasts and mitochondria, enhancing photosynthetic capacity, increasing antioxidant enzyme activity and the content of osmoregulatory substances. These changes may be related to the enhanced expression of calcium signal transmission and the synthesis of nitric oxide (NO), polyamines and jasmonic acid in the root system under saline-alkali stress.DiscussionOur findings partially explain the physiological and molecular mechanisms by which Pro-Ca enhances the tolerance and adaptability of mung bean plants to saline-alkali stress. This may become an effective strategy for the utilization of saline-alkali soil.